Antibiotic Considerations in the Management of Pediatric Open Fractures: Current Concept Review - Garcia-Lopez, Edgar; Vutescu, Emil Stefan; Orman, Sebastian; Schiller, Jonathan; Eberson, Craig P.; Cruz, Aristides I. (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Open fractures represent 2–9% of all pediatric fractures. Standard treatment in the Emergency Department (ED) includes prompt administration of intravenous antibiotics and tetanus prophylaxis, bedside irrigation, and reduction or immobilization based on the fracture pattern. Recommendations for management of open fractures in the pediatric population are mostly based on a 1989 landmark study by Patzakis et al. which analyzed factors influencing infection rates in adults and ultimately concluded that Cefazolin was superior to fluroquinolones or no antibiotics. Subsequent studies regarding antibiotic administration in the pediatric population have been less evidence-based, often choosing antibiotic protocols based on physician discretion and institutional practice patterns. To our knowledge, there is no consensus regarding optimal antibiotic treatment protocols for pediatric open fractures. To that end, we set out to review the literature for current trends in antibiotic management of open pediatric fractures. We specifically reviewed antibiotic choice, length of treatment, and subsequent infection rates. Based on our review of the literature we found that Gustilo and Anderson Type I pediatric open fractures are generally managed with the administration of a first-generation cephalosporin (e.g. Cefazolin) within three hours of injury, bedside irrigation, and fracture stabilization in the emergency department. Types II & III fractures may be similarly managed with a first-generation cephalosporin and provisional bedside irrigation, and fracture stabilization; however, these fracture types require further debridement and fracture stabilization in the operating room. Additional gram-negative coverage (e.g. Gentamicin) is frequently added for Type 3 fractures, and in cases of farm injuries, anti-clostridial drugs such as penicillin may be added; the evidence supporting these practices, however, is lacking. Overall, we found a paucity of high-quality evidence regarding antibiotic management of open pediatric fractures.